DIGITAL DRAMATURGY: PERFORMANCE ON SIMULTANEOUS VIDEO CONFERENCES IN CLASSROOM CONTEXT DURING THE COVID-19 PANDEMIC - Sepang, Nurul Robbi; Sari Monik Agustin; Rizki Fillaili (ASPIKOM Jabodetabek Region, 2022)
The new norm era forces people to do all activities from home, including working and studying. Data shows a significant increase in internet use during the pandemic. Longer working time, more online meetings, and sometimes they can be done at the same time (simultaneous meeting). Then, how does the Self perform if it has to be